Pluronics-Based Drug Delivery Systems for Flavonoids Anticancer Treatment - Sylwia Ronka; Aleksandra Kowalczyk; Dagmara Baczyńska; Anna K. Żołnierczyk (Gels, 2023)
This research concerns the investigation of the preparation of polymeric nanocarriers containing a flavonoid—naringenin, xanthohumol or isoxanthohumol—based on Pluronics by the thin-film formation method. The size of the formed micelles and their stability upon dilution were evaluated using Dynamic light scattering (DLS) analysis; the high values of the drug loading and the encapsulation efficiency confirmed that the proposed systems of flavonoids delivery consisting of Pluronic P123 and F127 nanomicelles could effectively distribute the drug into tumour tissues, which makes these nanocarriers ideal candidates for passive targeting of cancer cells by the enhanced permeation and retention (EPR) effect. The in vitro cytotoxicity of proposed flavonoids in the Pluronic formulations was investigated by the SRB assay with human colon cancer cells. We designed mixed polymeric micelles, which was a successful drug delivery system for the case of naringenin not being able to enhance the bioavailability and cytotoxic activity of xanthohumol and isoxanthohumol. Furthermore, it was observed that the higher amount of polymer in the formulation achieved better cytotoxic activity.